Discussion on Practical Options for Territorial Dispute Settlement Mechanisms — Taking the Case of Pulau Ligitan and Pulau Sipadan as an Example - Xiao Liu (Studies in Law and Justice, 2023)
In order to better respond to and deal with territorial disputes, and choose a more rational and appropriate dispute settlement mechanism, this article selects the case of sovereignty dispute between Indonesia and Malaysia over Pulau Ligitan and Pulau Sipadan for analysis, which chose two different dispute settlement mechanisms, namely, bilateral negotiation and judicial settlement, respectively, in the early and late stages of the dispute. The article analyzes the reasons for Indonesia’s two different choices at three levels: international system level, domestic level and decision-makers level, and finally draws the conclusion that Indonesia’s choice of territory dispute settlement methods was not only restricted by the structure, but also directly affected by the factors at the unit level to a large extent. It is in Indonesia’s interest to peacefully resolve the dispute over the two islands under structural pressure. And in this case, the 1997 Asian financial crisis and the ensuing crisis of governance ultimately prompted Indonesia to choose the International Court of Justice. The role played by the state and decision-makers in this case was more direct and critical.